OPTIMALISASI BIMBINGAN BELAJAR DENGAN STRATEGI KISS ME MY DARLING UNTUK MENINGKATKAN AKTIVITAS BELAJAR DI SMP NEGERI 10 BANDAR LAMPUNG - Sunanto Sunanto (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2014)
This classroom action research is aimed at seeing causes of socio economy factors and cognitive competence as seen on students ’ achievement. Data are collected using process approach which are based upon questionnaire and observatiom guide. The subjects are the 30 of the IX grade students of SMPN 10 Bandar Lampung. The study runs for three cycles conducted from July to September 2008 involving four teachers as collaborators. The learning method using --KISS ME MY DARLING-- can improve and motivate learning activities and the achievement.